New Optical Stochastic Solutions for Kundu–Mukherjee–Naskar Model With Random Variable Coefficients Using Two Different Methods - Mohammed, Wael W.; Al‐Askar, Farah M. (Mathematical methods in the applied sciences, 2025)
ABSTRACT In this paper, we examine the stochastic Kundu–Mukherjee–Naskar (SKMN) equation disturbed by multiplicative noise in the Itô sense. To convert the SKMN to another Kundu–Mukherjee–Naskar equation with random variable coefficients, we implement the necessary transformation. We employ two different approaches, the modified extended tanh function method and the Jacobi elliptic functions method, to provide novel trigonometric, hyperbolic, and rational solutions for KMNE‐RVCs. Following that, we can get the SKMN solutions. Additionally, some earlier results are generated. Furthermore, we give various graphical representations to demonstrate the impact of multiplicative noise on the exact solutions of the SKMN.